Strategies of the Ministry of Religious Affairs and the School Principal for Improving Teacher Performance at Madrasah Aliyah Negeri 7 Bireuen - Haekal, T. M.; Yusuf, Muhammad; Azmi, Khairul; Idris, M. Irwan; Fitri, Mutia (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2025)
Improving teacher performance in the school is one of the main focuses in achieving the goal of quality education. The purpose of this study was to analyze the strategies of the school principal and the Ministry of Religion in improving teacher performance at State Madrasah Aliyah 7 Bireuen. This study uses a qualitative descriptive method to explore the phenomena that occur in the field, focusing on the role of the school principal in motivating and improving the quality of teacher work through coaching, supervision, and rewarding. The researcher also analyzed the advantages and disadvantages of implementing the strategies applied to identify supporting and inhibiting factors that affect teacher performance. The results of the study indicate that the principal of State Madrasah Aliyah 7 Bireuen has implemented various effective strategies, such as teacher performance coaching, supervision, motivation, and ongoing training. However, there are still several challenges, such as lack of motivation from some teachers, high levels of stress due to administrative burdens, and lack of skills in the field of information technology. Nevertheless, training and support programs provided by the Ministry of Religious Affairs and effective communication from the principal have contributed to improving teacher professionalism. Therefore, a more comprehensive and sustainable approach is needed to overcome existing challenges and encourage improved teacher performance in the future.